Fluid-particle interaction with buoyancy forces on jeffrey fluid with newtonian heating - Abdul Rahman, Mohd Kasim; Nur Syamilah, Arifin; Syazwani, Mohd Zokri; Mohd Zuki, Salleh (Penerbit Akademia Baru, 2019)
The numerical results of fluid flow problem that being embedded with the dust particles is presented in this paper. In order to analyze such problem, a two-phase model is constructed by introducing a fluid-particle interaction forces in the momentum equations of fluid and dust phases. The buoyancy forces and aligned magnetic field are considered on the fluid flow. Also, the Newtonian heating boundary condition is induced on the vertical stretching sheet. The suitable similarity transformation is applied to the governing equations of the model which then produces the ordinary differential system. The results are obtained by adapting the Runge-Kutta Fehlberg (RKF45) method whereby the solutions are interpreted in terms of velocity and temperature profiles for Jeffrey fluid and dust particles respectively. The influences of assorted physical parameters are visualized graphically to clarify the flow and heat transfer characteristic for both phases. The discovery found that the presence of the dust particles have an effect on the fluid motion which led to decelerate the fluid transference. The present flow model can match to the single phase fluid cases if the fluid particle interaction parameter is ignored.